An eco-friendly biorefinery strategy for xylooligosaccharides production from sugarcane bagasse using cellulosic derived gluconic acid as efficient catalyst. (October 2019) - Zhou, Xin; Zhao, Jianglin; Zhang, Xiaotong; Xu, Yong
Graphical abstract: Highlights: An novel process for producing XOS by using cellulosic-derived GA was designed. XOS yield of 53.2% was obtained by direct GA hydrolysis of SB. GA was directly prepared by subsequent enzymatic hydrolysis and fermentation. Abstract: A novel approach was proposed for the production of xylooligosaccharides by direct pre-hydrolysis using gluconic acid as catalyst. Maximum xylooligosaccharides (degree of polymerization 2–6) yield of 53.2% could be obtained in 60 min through 5% gluconic acid hydrolysis of sugarcane bagasse at 150 °C. Furthermore, the yield of glucose from solids following gluconic acid hydrolysis treatment was 86.2% after fed-batch enzymatic hydrolysis with 10% solids loading. Results indicated that gluconic acid pretreatment combined with enzymatic hydrolysis could be successfully applied to sugarcane bagasse substrate. Subsequently, glucose could be efficiently bio-oxidized to gluconic acid by Gluconobacter oxydans ATCC 621H with 93.1% yield, and sugarcane bagasse derived gluconic acid has been proved to be an effective catalyst for xylooligosaccharides production. In this study, xylooligosaccharides production from sugarcane bagasse by gluconic acid hydrolysis demonstrated a great potential with respect to the production of these probiotics around the world.